The Paltera of Miagao, Iloilo social status of women as health providers. - Flores, Eleza F. (1997.)
With the premise that gender relations shape the role of women health providers in their rspective communities, this study recognizes that the paltera roles of selected women is significant in the villages of Miagao., This traditional birth attendants have persisted as the providers of unique methods in child delivery and more comprehensive and perssonalized support for mothers. In addition, their status indicators (age, length of service, civil status, residency and proficiency) justify their continuity despite the active health care program of the officially-endorsed rural health practitioners (i.e. the midwives). The life history of teh three birth attendants dramatizes the way by which their being female has affected their role in health-care-related activities. Their roles and services contribute to the advancement of theiir status within their respective homes; as well, these have allowed for a greater cope of tehir community involvements, despite the prevailing patriarchal orientation of Filipino culture and society and its devaluation of women's work.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: Women -- Health Providers; Paltera